Current Role of Radiation Therapy for Multiple Myeloma - Talamo, Giampaolo; Dimaio, Christopher; Abbi, Kamal K. S.; Pandey, Manoj K.; Malysz, Jozef; Creer, Michael H.; Zhu, Junjia; Mir, Muhammad A.; Varlotto, John M. (Frontiers in Oncology, 2015)
BACKGROUND: Radiation therapy (RT) is a treatment modality traditionally used in patients with multiple myeloma (MM), but little is known regarding the role and effectiveness of RT in the era of novel agents, i.e, immunomodulatory drugs (IMiDs) and proteasome inhibitors (PIs). METHODS: We retrospectively reviewed data from 449 consecutive MM patients seen at our institute in 2010-12 to assess indications for RT as well as its effectiveness. Pain response was scored similarly to RTOG 0631 and used the numerical rating pain scale (NRPS). RESULTS: Among 442 evaluable patients, 149 (34%) patients and 262 sites received RT. The most common indication for RT was palliation of bone pain (n=109, 42%), followed by prevention/treatment of pathological fractures (n=73, 28%), spinal cord compression (n=26, 10%), and involvement of vital organs/extramedullary disease (n=25, 10%). Of the 55 patients evaluable for pain relief, complete and partial responses were obtained in 76.4% and 7.2% respectively. Prior RT did not significantly decrease the median number of peripheral blood stem cells collected for autologous transplant, even when prior RT was given to both the spine and pelvis. Inadequacy of stem cell collection for autologous stem cell transplant (ASCT) was not significantly different and it occurred in 9% and 15% of patients receiving no RT and spine/pelvic RT, respectively. None of the 3 cases of therapy-induced AML/MDS occurred in the RT group. CONCLUSIONS: Despite the introduction of novel effective agents in the treatment of MM, RT remains a major therapeutic component for the management in 34% of patients, and it effectively provides pain relief while not interfering with successful peripheral blood stem cell collection for ASCT.